Life coaching following haematopoietic stem cell transplantation: a mixed‐method investigation of feasibility and acceptability. (25th February 2015) - Kenyon, M.; Young, F.; Mufti, G.J.; Pagliuca, A.; Lim, Z.; Ream, E.
<x xml:space="preserve">Abstract</x> Haematopoietic stem cell transplantation (HSCT) cures many haematological cancers. Recovery post‐HSCT is physically and psychologically challenging, lasting several months. Beyond the first post‐transplant year, a fifth report difficulties encompassing practical, social and emotional domains, including finance and employment. We investigated the feasibility, acceptability and impact of a life coaching intervention designed to address psychosocial 'survivor' concerns of HSCT recipients and facilitate transition to life post‐treatment. A concurrent embedded experimental mixed‐method design was employed. Pre‐ and post‐intervention data collection comprised qualitative semi‐structured telephone interviews and quantitative postal questionnaires. Seven purposively sampled HSCT recipients (<18 months) participated, reporting on one‐to‐one life coaching delivered by a professional life coach fortnightly over 8 weeks. Participants reported less anxiety, depression and fewer survivor concerns post‐intervention, with a trend for lower social difficulties and increased functional well‐being. Perceived self‐efficacy was unchanged. Life coaching was feasible to deliver and acceptable to the participants who indicated it was a positive experience, with benefits described in diverse areas including work, lifestyle and hobbies. Life coaching within cancer services potentially offers the means to address psychosocial concerns and support transition to life after treatment, enabling patients to reach their potential, e.g. returning to employment and financial independence. Further investigation of this intervention in cancer survivors is warranted.